PENANGANAN PROLAPS VAGINA PADA SAPI BALI DENGAN POLA ITERRUPTED HORIZONTAL MATTRESS - Pradana, I Made Yoga Windu; Purnama, Dewa Ketut Raeyadi; Murdayasa, I Wayan Gede; Handika, Dewa Gede Crisna Ari; Guna, I Putu Sandika Arta (Jurnal Sains dan Teknologi Industri Peternakan, 2026)
Vaginal prolapse is the protrusion of the vaginal mucosa from its anatomical position. Prompt and appropriate management is essential to prevent tissue necrosis. This paper discusses a case of vaginal prolapse in a Bali cow found in Kesiman Village, East Denpasar District, Bali. The affected cow was pregnant, with the vaginal mucosa observed hanging over the vulva. Treatment involved placing the cow in a restraint cage, cleaning the exposed vaginal mucosa with running water, and repositioning it to its normal position. This was followed by suturing the vulvar labia using an interrupted horizontal mattress pattern with nylon sutures to prevent recurrence. The sutures were removed 10 days post-treatment, and no signs of recurrent vaginal prolapse were observed.